2015
DOI: 10.1017/s1751731114002821
|View full text |Cite
|
Sign up to set email alerts
|

The influence of providing perches and string on activity levels, fearfulness and leg health in commercial broiler chickens

Abstract: The aim of this study was to assess the effect of providing environmental enrichment in the form of perches and string on the behaviour and welfare of commercial broiler chickens. Houses containing~23 000 broiler chickens were assigned to one of four treatments in a 2 × 2 factorial design. Treatments involved two levels of access to perches (P) (present (24/house) ' +P' or absent ' −P') and two levels of access to string (S) (present (24/house) ' +S' or absent ' −S'). All houses contained windows, and 30 straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 30 publications
6
44
4
1
Order By: Relevance
“…to their high weight and unbalanced bodies, an initial interest in perching followed by a decline as the birds gain weight could be expected (Bokkers & Koene 2003). This was confirmed by results in this study and previous studies investigating perching behaviour in fastgrowing broilers, as perching was found to decrease with increasing age (Bizeray et al, 2002;Bailie & O'Connell, 2015;Wallenbeck et al, 2016). Furthermore, previous studies have found that increasing body weight can inhibit broilers from performing behaviours that are highly motivated, which may lead to frustration in the birds (Bokkers et al, 2007) and thereby reduce their welfare (Jensen & Toates, 1993;Olsson & Keeling, 2000).…”
Section: Daytime Resting Behaviour and Positionsupporting
confidence: 89%
See 1 more Smart Citation
“…to their high weight and unbalanced bodies, an initial interest in perching followed by a decline as the birds gain weight could be expected (Bokkers & Koene 2003). This was confirmed by results in this study and previous studies investigating perching behaviour in fastgrowing broilers, as perching was found to decrease with increasing age (Bizeray et al, 2002;Bailie & O'Connell, 2015;Wallenbeck et al, 2016). Furthermore, previous studies have found that increasing body weight can inhibit broilers from performing behaviours that are highly motivated, which may lead to frustration in the birds (Bokkers et al, 2007) and thereby reduce their welfare (Jensen & Toates, 1993;Olsson & Keeling, 2000).…”
Section: Daytime Resting Behaviour and Positionsupporting
confidence: 89%
“…Heat sources over the perches and records of the duration and number of resting bouts and the behaviour following a disturbance event would have added value to the study. Furthermore, as perching frequency in fast-growing broilers declines around week five (Bailie & O'Connell, 2015;Bizeray et al, 2002), it would have been beneficial to record each behavioural assessment type on broilers younger than this.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…It is also possible that young broilers were more fearful, which led to a longer initial period of behavioural suppression before frolicking and sparring occurred. Fearfulness was not measured throughout the cycle in this study, however previous similar research has found that birds became less fearful as they aged (Bailie and O'Connell, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, the results are in accordance with Laurence et al, (2015), it was reported that EE affected the activities of the quails. It was reported that EE, which was applied on Beijing ducks, caused a reduction in undesired behaviors comparing to ones, on which EE wasn't applied (Colton and Fraley, 2014), and might reduce conspecific pecking behavior at laying hens, thus weakening the injuries (Daigle et al, 2014), and also EE, created using straw bales, had potential necessary to increase welfare of animals (Bailie and O'Connell, 2015).…”
Section: Resultsmentioning
confidence: 99%